ISLAM DAN MODERNITAS : Penafsiran Muhammad Ḥusain Ṭabāṭabāʾī dalam Al-Mīzān fī Tafsīr al-Qur'ān - Robby Hidayatul Ilmi (STAI AL-ANWAR SARANG, 2024)
This article aims to examine Muhammad Ḥusain Ṭabāṭabāʾī’s reaction to modernity in Tafsīr al-Mīzān fī Tafsīr al-Qurʾān, contextualizing it within the wider discourse of Muslim discussions on rationality, empiricism, and secularization. The research utilizes a qualitative, library-based methodology centered on intellectual history. The principal source, al-Mīzān, is analyzed thematically and later organized according to Abdullah Saeed’s paradigm of “modernist tafsir” to discern patterns of adoption, negotiation, and critique of modernity. The results suggest that Ṭabāṭabāʾī embodies a dual stance. He incorporates certain contemporary features, like a critical perspective on tradition, rational and linguistic methodologies, inter-sectarian openness, and a pronounced focus on interpreting the Qurʾān through the Qurʾān (tafsīr al-Qurʾān bi al-Qurʾān). Conversely, he rigorously challenges scientific reductionism and the subjugation of revelation to Western empirical epistemology. Rooted on the philosophy of al-ḥikmah al-mutaʿāliyah, he safeguards the metaphysical and mystical aspects of the Qurʾān while remaining receptive to rational discourse with contemporary ideas. This paper advances the field by illustrating that answers to modernity within the Shiʿi tradition are diverse, presenting a form of critical synthesis between rationality and transcendence. In this regard, Ṭabāṭabāʾī illustrates the potential for a Qurʾānic interpretive epistemology that is both contemporary and critically defiant of Western intellectual dominance.